2014
DOI: 10.1007/978-1-4939-1438-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to Study Epigenetic Control and the Epigenome in Parasites

Abstract: Epigenetics is the study of heritable changes in gene expression that occur independent of the DNA sequence. Due to their intimacy with DNA, histones have a central role in chromatin structure and epigenetic regulation. Their tails are subject to posttranslational modifications (PTMs) that together with chromatin-remodeling proteins control the access of different proteins to DNA and allow a precise response to different environmental conditions. The first part of this chapter is dedicated to histone enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In previous work, we applied ChIP-chip to T. gondii and showed that the distributions of epigenomic modifications on chromatin are conserved in protozoa [ 22 ]. We standardized native chromatin immunoprecipitation (N-ChIP) for T. gondii using native DNA without crosslinking digested with Micrococcal nuclease (MNase) followed by next generation sequencing [ 23 ]. The digested fragments of around 150–200 bp represent nucleosomal DNA, as verified by nucleosome mapping of input DNA.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we applied ChIP-chip to T. gondii and showed that the distributions of epigenomic modifications on chromatin are conserved in protozoa [ 22 ]. We standardized native chromatin immunoprecipitation (N-ChIP) for T. gondii using native DNA without crosslinking digested with Micrococcal nuclease (MNase) followed by next generation sequencing [ 23 ]. The digested fragments of around 150–200 bp represent nucleosomal DNA, as verified by nucleosome mapping of input DNA.…”
Section: Resultsmentioning
confidence: 99%
“…A native MNase-ChIP-seq technique was used as described previously ( 44 ). The resulting DNA fragments were aligned to the T. brucei 427 reference genome, and peaks of enrichment were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Core histones were extracted using an acid extraction protocol adapted for T. brucei ( 44 ). In brief, 1 × 10 10 and 1 × 10 9 cells/sample were harvested for BF ( n = 11) and PF ( n = 9) trypanosomes, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a strategy would regulate the expression of genes involved in pathogenicity, differentiation in the life cycle, and other vital aspects of the pathogen. Therefore, identifying new epigenetic targets would contribute immensely to controlling or even eradicating these diseases [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%